2017
DOI: 10.3141/2641-01
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive In Situ Characterization of Elastic Moduli of Full-Depth Reclamation Base Mixtures

Abstract: State highway agencies are searching for more cost-effective methods for rehabilitating roads. One sustainable solution is full-depth reclamation (FDR), which is a pavement rehabilitation technique that involves pulverizing and reusing materials from existing distressed pavements in place. However, there is little information on the long-term properties of these recycled materials. An important property, the elastic modulus, indicates the structural capacity of pavement materials and is highly recommended for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Following AASHTO's recommendations, the back-calculated modulus (E FWD ) obtained from deflection data were adjusted to laboratory conditions of resilient modulus for M-E design by applying a coefficient of 0.62 (24). The resilient modulus of FDR obtained in this project have more variability that the ones found in the literature, with values ranging from 38 to 50 kips per square inch (ksi) for non-stabilized FDR and 48 to 112 ksi for emulsion-stabilized FDR (12,16,23,26). This variability may be a result of compounding factors including the variability of FWD testing, the back-calculation process, and, even more importantly, the variability related to the in-place recycling process of FDR (27,28).…”
Section: Back-calculated Modulus From Falling Weight Deflectometer (Fwd)mentioning
confidence: 41%
See 4 more Smart Citations
“…Following AASHTO's recommendations, the back-calculated modulus (E FWD ) obtained from deflection data were adjusted to laboratory conditions of resilient modulus for M-E design by applying a coefficient of 0.62 (24). The resilient modulus of FDR obtained in this project have more variability that the ones found in the literature, with values ranging from 38 to 50 kips per square inch (ksi) for non-stabilized FDR and 48 to 112 ksi for emulsion-stabilized FDR (12,16,23,26). This variability may be a result of compounding factors including the variability of FWD testing, the back-calculation process, and, even more importantly, the variability related to the in-place recycling process of FDR (27,28).…”
Section: Back-calculated Modulus From Falling Weight Deflectometer (Fwd)mentioning
confidence: 41%
“…This study included laboratory and field performance evaluations that showed a good performance of the pavement 4 years after construction and derived recommendations of M-E level 1 and level 2 inputs for cement-stabilized FDR. Amarh et al investigated three FDR projects that included foamed, asphalt emulsion and cement stabilizers to analyze changes in the elastic modulus over time and its sensitivity to temperature and seasonal effects (12). The authors found that the backcalculated modulus of FDR bases increased over time and they developed regression models to predict the short-term strength gains.…”
Section: Current State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations